Age-, sex-, and maturity-associated variation in the phase angle after adjusting for size in adolescents - de Moraes, Anderson M.; Quinaud, Ricardo T.; Ferreira, Giovana O. C.; Lima, Ahlan B.; Carvalho, Humberto M.; Guerra-Júnior, Gil (Frontiers in Nutrition, 2022)
Applied research using phase angle (PhA) in children and adolescents has increased notably. We examined the relationships between PhA, age, sex, biological maturity status, and body size in 10–16-year-old adolescents, using multilevel modelling in a fully Bayesian framework. The sample comprised 519 adolescents (female, n = 241; male, n = 278) from Campinas, São Paulo, Brazil. Biological maturity status was assessed with self-examination of pubertal development for sexual maturity and maturity offset protocol to estimate age at peak height velocity (PHV) for somatic maturity status. Stature and body mass were measured by anthropometry. Phase angle was calculated based on raw resistance and reactance values (50 kHz frequency) obtained by bioelectrical impedance with foot-to-hand technology. The multilevel regression analysis revealed boys had significantly higher values than girls, adjusting for age group and sexual maturity status. Overall, older and more mature adolescents had higher values of phase angle. When considering aligning variation in phase angle by distance to estimated PHV (maturity offset), there was a higher association between phase angle and time before and after predicted age at PHV for boys (r = 0.31, 90% credible interval: 0.23 to 0.39) than girls (r = 0.20, 90% credible interval: 0.11 to 0.28). When including body mass in the multilevel models corresponding changes in overall body mass mediate most of the inﬂuence of maturity status and age group on phase angle. The present study demonstrated that the variability in phase angle is related to inter-individual variation in sex, age, and maturity status, as well as differences in body size. Research with adolescents considering phase angle should use multilevel modeling with standardized parameters as default to adjust for the concurrent influence of sex, age, maturity status, and body size.